PENGARUH MODEL PEMBELAJARAN KONTEKSTUAL DAN APLIKASI CANVA TERHADAP MOTIVASI BELAJAR SISWA PADA MATERI BILANGAN KELAS 5 SD GMIM LALUMPE - Juliana Margareta Sumilat; Gloria Ritsita Lengkong (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Learning motivation is a crucial factor in achieving academic success, particularly in mathematics, which is often perceived as challenging by elementary students. This study aims to examine the effect of the Contextual Teaching and Learning (CTL) model integrated with the Canva application on the learning motivation of fifth-grade students at SD GMIM Lalumpe. The study employed a quantitative approach using a quasi-experimental design with a pretest-posttest control group. The results showed a significant increase in learning motivation among students taught using CTL assisted by Canva compared to those taught conventionally. These findings indicate that contextual learning combined with interactive digital media can enhance student motivation and engagement in mathematics learning.